Evaluasi Usability pada ¬E-Theses Institut Agama Islam Negeri (IAIN) Kediri Menggunakan Metode USE Questionnaire - Muhamad Abdul Muid; Firman Jati Pamungkas; Wahyu Hariyanto (UIN Maulana Malik Ibrahim Malang, 2022)
College library is required to improve the quality and quantity of their services. One of the efforts made by IAIN Kediri Library is the existence of E-Theses IAIN Kediri. E-Theses IAIN Kediri is expected to give easiness for IAIN Kediri student to access scientific work of civitas academica. However, students still find it difficult. Therefore usability evaluation on E-Theses IAIN Kediri is necessary to fix the problem. In this study the method used is the USE Questionnaire where has 4 variables, i.e. usefulness, ease of use, ease of learning, and satisfaction. The purpose of this study is to find the results of usability evaluation on E-Theses IAIN Kediri and the repair result. After usability evaluation, improvement suggestions are given matching the repair result. In this study, the results of usability evaluation on E-Theses IAIN Kediri for the usefulness variable obtained value of 3,76, ease of use variable obtained value of 3,50, ease of learning variable obtained value of 3,61, and satisfaction variable obtained value of 3,60. Based on the results of task scenario and addition questions, there is a problem like can't find scientific work as the wish, not have a user guide, confusing user interface, and feature not working properly. Therefore, improvement suggestions are given about repair the user interface, adding a complaint feature, information about user guide, user education, and improvement suggestion about library policyKeywords: USE questionnaire, Usability evaluation, E-Theses IAIN Kediri